Implementation of an Orthopaedic Triage Service for Osteoarthritis in the New Zealand Health System: A Retrospective Audit - Stilwell, JA; Reid, D; Larmer, P (The New Zealand Journal of Physiotherapy, 2024)
Orthopaedic triage services led by advanced physiotherapy practitioners (APPs) have been shown to be effective health care models in the management of osteoarthritis. Despite this, New Zealand health systems have only recently begun to implement and evaluate these models of care. The implementation of the community orthopaedic triage service (COTS) within the Bay of Plenty District Health Board (BOPDHB) was piloted to improve the patient journey through the health system by providing earlier assessment and referral to the most appropriate intervention. This retrospective audit analysed data collected from patients assessed in the COTS and orthopaedic outpatients between September 1 2020 to September 1 2021. Results show the COTS saw 49–52% of the volume of patients referred to orthopaedic outpatients. The mean (SD) wait time to be seen in the COTS was 37.3 (32.8) days compared to 157.7 (56.2) days in orthopaedics. Eighty per cent of patients referred to orthopaedics from the COTS were appropriate for first specialist appointment with 65% being listed for surgery by an orthopaedic surgeon. Adoption of these pathways has the potential to facilitate earlier assessment and access to intervention, thus improving the musculoskeletal health of New Zealanders.
Keywords: 1103 Clinical Sciences; 4201 Allied health and rehabilitation science